A New Approach to Ring Expansion of Keto Aziridines to 2,5-Diaryloxazoles - Samimi, Heshmat A.; Mohammadi, Somaye (Synlett, 2013)
Ring expansion of keto aziridines to the corresponding 2,5-diaryl oxazoles in the presence of dicyclohexyl carbodiimide and iodine under refluxing acetonitrile conditions is described. A plausible mechanism is proposed.
Keywords: ring expansion; keto aziridine; oxazole